The e-QuoL project: enhancing long-term follow-up care for childhood cancer survivors through digital innovation, results of an exploratory questionnaire - Requier, Romane; Gimenez, Clara; Muraca, Monica; Lähteenmäki, Päivi M.; Gresle, Anne-Sophie; Henriksen, Louise Tram; Marion, Beauchesne; Benoit, Gerfault; Thornton, Kristen E. T.; Demoor-Goldschmidt, Charlotte (SPRINGER, 2026)
Purpose
Childhood, adolescent, and young adult cancer survivors represent a growing population with unique long-term follow-up (LTFU) needs, including managing late effects of treatment and ensuring psychosocial well-being. The e-QuoL project aims to develop digital tools tailored to enhance survivorship care.
Method
An online survey comprising 424 questions was distributed across 16 European countries. The distribution plan ensured engagement from diverse stakeholders, including patients, parents, and healthcare professionals. Descriptive and thematic analyses of survey data identified key content, functionalities, and features for the design of such tools.
Results
For participants (n = 53), the inclusion of a follow-up plan for the risk of sequelae in the first 5 years of follow-up was the highest priority (mean score, 9.62). Supportive care items were deemed important. In terms of functionalities, the most highly rated was the ability to send reminders to patients to not forget exams (mean score, 9.25). The inclusion of an algorithm to propose follow-up plans based on selected sections was also particularly valued (mean score, 9.10). Finally, the user experience of digital tools, including the need for these tools to be engaging, easy to use, and customizable, was highlighted by 66.7% of participants.
Conclusion
This study emphasizes the need for customizable, accessible, and user-centered digital tools to bridge disparities in LTFU care. Collaborative efforts to address technological, financial, and ethical barriers are essential to achieving equitable, effective survivorship support.
Implications for Cancer Survivors
By developing and implementing comprehensive digital tools, a more personalized, holistic, and effective model of survivorship care can be achieved.